Differentiation of supporting methods of business informatics teaching offered by selected educational portals - Owoc, Mieczysław; Hołowińska, Katarzyna (Zróżnicowanie wspomagających metod nauczania informatyki w biznesie oferowanych przez wybrane portale edukacyjne, 2018)
Nowadays Internet technologies are becoming more capable of supporting traditional ways of teaching. Education portals in particular offer lessons in various domains as supportive means for experienced tutors to deliver knowledge to students. The aim of this study is to present the solutions offered by various educational centres and to analyse supportive methods of teaching. The paper presents. A discussion about the approaches to the formulation of a list of teaching methods supporting traditional lessons. The next part is devoted to an overview of selected educational portals offering courses in the business informatics area. Then the paper concerns the comparison of the applied methods of teaching which support classic lessons. The utility of particular methods in teaching selected courses is demonstrated and evaluated according to the defined survey assumptions. Finally, suggestions concerning the hybridisation of various supporting teaching methods are proposed
Informatyka Ekonomiczna = Business Informatics, 2018, Nr 2 (48), s. 54-66
Keywords: educational methods; e-portals; effective education; metody edukacji; e-portale; efektywna edukacja